PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN EKONOMI SMA NEGERI 4 PEKANBARU - Intan Aprilliany; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Education is a main factor in shaping the good of the human person. Education is gained not only in schools but all factors can be used as a source of education. Especially the environment that plays a role or influence on student learning outcomes. With the development of the times, technology is growing rapidly. The world of education today has also begun to integrate technology in various aspects including in learning. Education policy is directed to the use of technology so as to prepare human resources capable of facing global challenges. The purpose of this research is to knowing the effect of utilization of information technology on student learning outcomes in Economics lesson SMA Negeri 4 Pekanbaru. The population in this study were students of class X IIS SMA Negeri 4 Pekanbaru as many as 156 people, and who became the sample are 61 people. Data measurement using questionnaire. Analysis of data used is simple linier regression. The result of the research based on simple linear regression showed that the utilization of information technology had an effect on the student learning outcomes of class X IIS SMA Negeri 4 Pekanbaru. This can be seen from constanta value (a) of 70,833 and regression coefficient (b) 0,269 with regression equation 70,833 + 0,269 . Seen from the calculation of R2 (R Square Change) obtained a value of 0,504. This is means that the contribution of the use of information technology to student learning outcomes of 50.4%Keywords: Utilization of Information Technology, Student Learning Outcomes